2009
DOI: 10.1093/tropej/fmp012
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Levels in Children with Congenital Heart Disease

Abstract: Circulating ghrelin level was elevated in children with congenital cyanotic and acyanotic heart disease, and was associated with a decrease in BMI. This elevation in ghrelin level may represent malnutrition and growth retardation in those patients as obvious by anthropometric measures too. This may suggest that ghrelin may have an important role as a compensatory mechanism in the regulation of the metabolic balance in them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 41 publications
2
11
1
1
Order By: Relevance
“…Kandil et al . concluded that circulating ghrelin level was increased in children with CCHD and ACHD, and was correlated with a decline in BMI, which is consistent with the present results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Kandil et al . concluded that circulating ghrelin level was increased in children with CCHD and ACHD, and was correlated with a decline in BMI, which is consistent with the present results.…”
Section: Discussionsupporting
confidence: 92%
“…Functionally, IL‐6 is involved in acute phase response and has a wide spectrum of effect, from induction of chronic inflammation and endothelial cell dysfunction to fibrogenesis and disruption of autoimmunity . Recently, an increasing number of studies have assessed the correlation of CHD with serum ghrelin, TNF‐α and IL‐6, but the results have been inconclusive. Therefore, we designed a new case–control study to investigate the correlation of CHD with serum ghrelin, TNF‐α and IL‐6, and then combined the results with a meta‐analysis of relevant studies to obtain a more definitive and conclusive estimate of the association of ghrelin, TNF‐α and IL‐6 with CHD.…”
mentioning
confidence: 99%
“…Açlık hormonu olarak bilinen ghrelin, malnütrisyon ve büyüme geriliğindeki enerji metabolizmasındaki eksikliği dengelemek üzere artar. Doğuştan kalp hastalığı olan çocuklarda serum ghrelin düzeylerinin yüksek olduğu ve ghrelin düzeyleri ile VKİ arasında negatif ilişki olduğu gösterilmiştir (31,32). Sık geçirilen enfeksiyonlar DKH'lı çocuklardaki büyüme geriliği ve malnütrisyon gelişiminin en önemli nedenlerinden birisidir (6,28).…”
Section: Discussionunclassified
“…In a recent study in Egypt, 18 infants with CCHD (ten with tetralogy of Fallot, four with tricuspid atresia and four with pulmonary atresia), in comparison to ageand sex-matched healthy controls, had a mean weight and height at 46 and 81%, respectively, of their counterparts. 66 Chronic hypoxia also influences growth. In a lamb model of chronic hypoxia, the pulmonary artery was partially occluded and an atrial septostomy performed to create an aortic oxygen saturation of 60-74%.…”
Section: Intestinal Microbiota and Probiotics: Potential Role In Termmentioning
confidence: 99%